(untitled) (Journal of Pharmaceutical Negative Results, 2023)
BACKGROUND The geriatric population of India is growing at higher rate than general population. Few studies have been carried out in geropsychiatric group of patients in India. This study was planned to evaluate sociodemographic and clinical profile of geriatric patients in tertiary hospital in a city of central India. MATERIAL AND METHODS In this retrospective clinical study, all geriatric patients of above 60 years of age attending the general psychiatry out-patient department between June-August 2015 in a city of central India were included. Semi-structured sociodemographic and clinical profile collection pro forma and international classification of diseases-10 (ICD-10) were used as tool and statistical analysis was done by using SPSS 16. RESULTS The results showed that among the total 2819 patients attended the psychiatric OPD, there were 311 geriatric patients (11%) with psychiatric morbidity. Most of them were married, illiterate, unemployed and Hindu by religion and residing in joint family in an urban locality. Depression was commonest (n=75; 24.1%) followed by dementia (n=51; 16.4%), generalized anxiety disorder (n=47; 15.1%), schizophrenia and other psychosis (n=46; 14.8%) and bipolar disorder (n=36; 11.6%). CONCLUSION In this study, depression was found to be the most common psychiatric morbidity like earlier studies but overall prevalence of psychiatric morbidity amongst elderly in this study was found to be less in comparison to those reported in previous studies from India. The prevalence of psychiatric illness in the older population expected to rise dramatically in coming decades in India.